Ultraviolet long-afterglow nano-luminescent material and preparation method thereof
By doping cesium ions and halogen anions in NaLuF4:Gd3+ nanocrystals, the trap depth and density are regulated, and the problem of single traps and insufficient density of rare earth-doped fluoride long afterglow materials is solved, which significantly improves the luminous efficiency and afterglow duration, and enhances its application potential.
Patent Information
- Application Number
- CN202510028588.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The existing rare earth doped fluoride long afterglow materials have a single trap depth and insufficient trap density, resulting in unsatisfactory luminescence performance and short afterglow time, making it difficult to meet the needs of certain specific applications.
Trap depth and density are regulated by doping cesium ions Cs+ and/or bromide ions Br- and/or iodine ions I- in NaLuF4:Gd3+ nanocrystals to improve luminescence performance and afterglow intensity.
The luminescence efficiency and afterglow duration of ultraviolet afterglow nanoluminescent materials have been significantly improved, and its application potential in information security encryption and storage is enhanced.
Smart Images

Figure CN119823759A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of long afterglow luminescent materials, in particular to an ultraviolet long afterglow nano luminescent material and a method for enhancing the ultraviolet long afterglow of rare earth doped fluoride by co-doping cesium ions and anions. Background Art
[0002] Long afterglow materials are luminescent materials that can absorb a certain amount of excitation energy and store part of the energy, and release the energy in the form of light after the excitation stops. Afterglow occurs when the excited electrons reach the excited state or conduction band and migrate to the defect position through transfer or tunneling, resulting in delayed light emission. The generation of continuous luminescence refers to the process in which the excited electrons or holes are captured by defects and then continuously return to their initial ground state. These defect positions are usually called "traps", so the effective regulation of the traps, including their depth, density and distribution, is of great significance to improving the performance of long afterglow materials.
[0003] Among many long afterglow materials, rare earth doped fluorides have become an important material that has attracted much attention due to their excellent luminescence properties and chemical stability. This type of material is not only widely used in the fields of X-ray information storage and information encryption, but also shows broad application prospects in many fields such as bio-markers, luminous displays, and security signs. However, the rare earth doped fluoride long afterglow materials currently used have defects such as a single trap depth and insufficient trap density, which leads to unsatisfactory luminescence performance of rare earth doped fluoride long afterglow materials, short afterglow time, and difficulty in meeting the needs of certain specific applications, limiting the application of rare earth doped fluoride long afterglow materials in information security encryption and storage. Summary of the invention
[0004] Based on this, the object of the present invention is to provide an ultraviolet long afterglow nano luminescent material and a preparation method thereof.
[0005] The above-mentioned object of the present invention is achieved by the following technical scheme: an ultraviolet long afterglow nanoluminescent material, comprising a fluoride matrix and rare earth ions Gd doped in the fluoride matrix 3+ , the rare earth ion Gd 3+ The doping amount is 15-25 mol%; the fluoride matrix is ALuB4; wherein A is selected from Na or Cs x Na 1-x , x is the doping ion Cs + Relative alkali metal ion Na + The molar percentage coefficient; B is F 1-y Z y , y is the doping ion Z - Relative halogen ion F -The molar percentage coefficient has a value range of 0.01≤y≤0.04, and Z is selected from at least one of Br and I.
[0006] Compared with the prior art, the present invention adopts NaLuF4:Gd 3+ Cesium ions doped into nanocrystals + and / or bromide ion Br - and / or iodide ion I - , successfully regulated the trap depth and density in the ultraviolet long afterglow nanoluminescent materials, thereby improving the luminescence performance of the ultraviolet long afterglow nanoluminescent materials and significantly enhancing the afterglow intensity.
[0007] Furthermore, A is Cs x Na 1-x , the value range of x is 0.01≤x≤0.04.
[0008] Furthermore, the average particle size of the ultraviolet long afterglow nano luminescent material is 55nm-60nm.
[0009] Furthermore, the ultraviolet long afterglow nanoluminescent material exhibits 311nm down-conversion fluorescence under X-rays.
[0010] The present invention also provides a method for preparing an ultraviolet long afterglow nano luminescent material, comprising the following steps:
[0011] S10, mixing rare earth salt, octadecene and oleic acid in sequence, and heating to obtain a mixed solution;
[0012] S20, after the mixed solution is cooled to room temperature, a sodium source, a fluorine source, and a cesium source and / or a bromine source and / or an iodine source are added to the mixed solution to form a mixed solution, and the mixed solution is heated to a first temperature and kept stirred to obtain a preliminary product;
[0013] S30, heating the preliminary product to a second temperature, and maintaining stirring, and then continuing to heat to a third temperature under an inert gas environment, and maintaining the temperature, to obtain a final product;
[0014] S40, washing the final product to obtain an ultraviolet long afterglow nano-luminescent material;
[0015] The second temperature is greater than the first temperature, and the third temperature is greater than the second temperature.
[0016] Furthermore, in step S20, the mixed solution contains a sodium source, a cesium source, a bromine source and / or an iodine source, and a fluorine source in a molar ratio of 240-250:0-10:4-20:380-396.
[0017] Furthermore, in step S20, the first temperature is 45-55° C., and the stirring time is 20-40 minutes.
[0018] Furthermore, the rare earth salt is an acetate or chloride salt containing one or more rare earth elements, preferably an acetate, with a concentration of 0.2M.
[0019] Furthermore, the rare earth salt comprises lutetium acetate and gadolinium acetate in a molar ratio of 4:1, and the molar ratio of the rare earth salt to the sodium source is 5:4-13.
[0020] Furthermore, in step S10, the heating includes heating the mixed solution to 140-160° C. and continuously stirring at the temperature for 30 minutes.
[0021] Further, in step S30, the second temperature is 90-110° C., the stirring time is 20-40 minutes, the third temperature is 280-300° C., and the insulation time is 80-100 minutes.
[0022] Furthermore, in step S20, a sodium source, a cesium source, a bromine source, and a fluorine source are added to the mixed solution, and the molar ratio of the sodium source, the cesium source, the bromine source, and the fluorine source is 245:5:8-12:388-392.
[0023] Furthermore, the sodium source is sodium hydroxide with a concentration of 0.4 mmol / mL, dissolved in methanol solution.
[0024] Furthermore, the cesium source is cesium hydroxide with a concentration of 0.4 mmol / mL, dissolved in methanol solution.
[0025] Furthermore, the fluorine source is ammonium fluoride with a concentration of 0.5 mmol / mL, dissolved in methanol solution.
[0026] Furthermore, the bromine source is ammonium bromide with a concentration of 0.5 mmol / mL, dissolved in methanol solution.
[0027] Furthermore, the iodine source is ammonium iodide with a concentration of 0.5 mmol / mL, dissolved in methanol solution.
[0028] Furthermore, the introduced halogen anions are preferably bromide ions. Due to their large ionic radius, iodide ions are very easy to form hydrogen bonds with water molecules in the air. After being doped into the material, the water absorption of the material is increased, which is not conducive to long-term storage.
[0029] Furthermore, the average particle size of the nanocrystals obtained by S40 is about 58 nm, ranging from 55 to 60 nm, and it exhibits a down-conversion fluorescence of 311 nm under X-rays. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1For Cs under X-ray bombardment x Na 1-x Lu(F 1-y Z y )4: Gd 3+ Schematic diagram of the formation of internal defects in the lattice.
[0031] Figure 2 Cs in the preparation method of the present invention x Na 1-x Lu(F 1-y Z y )4: Gd 3+ Schematic diagram of nanocrystal synthesis.
[0032] Figure 3 Cs prepared in Example 3 of the present invention 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ Transmission electron microscopy image.
[0033] Figure 4 The Cs prepared in Example 3 of the present invention 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ Particle size distribution histogram.
[0034] Figure 5 Cs prepared in Example 1 0.02 Na 0.98 LuF4:Gd 3+ 20 mol% nanocrystals, Cs prepared in Example 3 0.02 Na 0.98 Lu(F 0.97 Br 0.03 )4: Gd 3+ 20 mol% nanocrystals, Cs prepared in Example 4 0.02 Na 0.98 Lu(F 0.99 Br 0.01 )4: Gd 3+ 20 mol% nanocrystals, Cs prepared in Example 5 0.02 Na 0.98 Lu(F 0.97 Br 0.03 )4: Gd 3+ 20 mol% nanocrystals, Cs prepared in Example 6 0.02 Na 0.98 Lu(F 0.96 Br 0.04 )4: Gd 3+20mol% nanocrystals and NaLuF4:Gd prepared in Comparative Example 1 3+ X-ray diffraction comparison pattern of 20mol% nanocrystals.
[0035] Figure 6 Cs prepared in Example 1 0.02 Na 0.98 LuF4:Gd 3+ 20 mol% nanocrystals, NaLu (F 0.98 Br 0.02 )4: Gd 3+ 20 mol% nanocrystals, Cs prepared in Example 3 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ 20mol% nanocrystals and NaLuF4:Gd prepared in Comparative Example 1 3+ Comparison of thermoluminescence curves of 20mol% nanocrystals.
[0036] Figure 7 Cs prepared in Example 3 0.01 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ The long-term afterglow decay curve of nanocrystals and the Cs prepared in Example 1 0.01 Na 0.98 LuF4:Gd 3+ Comparison of long-term afterglow decay curves of nanocrystals.
[0037] Figure 8 Cs prepared in Example 1 0.02 Na 0.98 LuF4:Gd 3+ 20 mol% nanocrystals, NaLu (F 0.98 Br 0.02 )4: Gd 3+ 20 mol% nanocrystals, Cs prepared in Example 3 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ 20mol% nanocrystals and NaLuF4:Gd prepared in Comparative Example 1 3+ Comparison of the radioluminescence of 20 mol % nanocrystals.
[0038] Fig. 9 The Cs prepared in Example 1 0.02 Na 0.98LuF4:Gd 3+ 20 mol% nanocrystals, NaLu (F 0.98 Br 0.02 )4: Gd 3+ 20 mol% nanocrystals, Cs prepared in Example 3 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ 20mol% nanocrystals and NaLuF4:Gd prepared in Comparative Example 1 3+ Comparison of afterglow decay curves of 20mol% nanocrystals. DETAILED DESCRIPTION
[0039] In order to solve the problem that the existing ultraviolet long afterglow nanoluminescent materials have a single trap depth and insufficient trap density, which limits the application of long afterglow materials in information security encryption and storage, the present invention intends to enhance the afterglow performance and luminescence performance of ultraviolet long afterglow nanoluminescent materials by regulating the defects of ultraviolet long afterglow nanoluminescent materials. Based on this, the present invention first screened the matrix and activator of the ultraviolet long afterglow nanoluminescent materials. Among them, NaLuF4 has the advantages of low phonon energy, large band gap and high X-ray absorption coefficient, which is suitable as a matrix, while Gd 3+ It can produce imperceptible pure ultraviolet radiation luminescence memory, suitable as an activator. Under X-ray excitation, the Frenkel defect center of fluorine is generated by substitution of F- from its original lattice displacement. These defects are likely to capture photogenerated charge carriers, as evidenced by the presence of occupied and vacant impurity energy levels near the valence and conduction band edges. After turning off the X-ray source, the trapped electrons and holes escape during thermal fluctuations and diffuse into the lanthanide activator through the host conduction band and valence band, respectively. Since the occupied 4f orbital resonates with the host valence band edge, Gd is likely to be formed during the hole relaxation process 3+ -hole complexes, which then combine with electron radiation to produce ultraviolet radiation. Therefore, rare earth doped fluoride NaLuF4:Gd 3+ Nanocrystals have good chemical stability, high quantum efficiency and adjustable luminescence properties, and are one of the ideal candidates for the research of ultraviolet long afterglow nanoluminescent materials.
[0040] Based on this, the present invention uses rare earth doped fluoride NaLuF4:Gd 3+ Based on nanocrystals, the influence of doping ions on the performance of nanocrystals is studied. First, the invention studies the influence of doping ions partially replacing Na ions on the luminescence performance and afterglow performance of rare earth doped fluorides. It is found that in NaLuF4:Gd 3+Doping nanocrystals with cesium ions helps improve the luminescence and afterglow properties of nanocrystals. The principle is that cesium ions have a larger atomic number than sodium ions, and their ability to absorb X-rays is relatively stronger. The equivalent replacement of sodium ions by cesium ions can increase NaLuF4:Gd 3+ The absorption capacity of nanocrystals for X-rays is also due to the fact that the ionic radius of cesium ions is larger than that of sodium ions. The distance between cesium ions and anions is reduced, resulting in a lower binding energy. Anions are more easily excited to the interstitial position to produce anion vacancies. However, only doping with cesium ions has no significant effect on NaLuF4:Gd 3+ The improvement of the luminescence and afterglow performance of nanocrystals is limited.
[0041] In view of the limitations of the above-mentioned single ion doping, the present invention further broadens the idea and explores the possibility of replacing F ions with multiple ions, as well as their synergistic effects with cesium ions or other potential ions. Figure 1 As shown, as halogen elements, bromide ions and iodide ions have larger ionic radius than fluoride ions. Partial replacement of fluoride ions by bromide ions will also lead to material lattice mismatch and reduced bond energy. Anions are more easily excited to interstitial positions, increasing trap density and trap depth, thereby significantly improving the luminescence efficiency and afterglow duration of ultraviolet long afterglow nanoluminescent materials.
[0042] However, the excessive introduction of cesium ions and halogen anions will cause changes in the crystal field environment that are not conducive to the luminescence of rare earth ions, affecting the luminescence performance. Therefore, the present invention further adjusts the doping ratio of cesium ions and halogen anions to ensure a positive impact on material properties and further improve material properties.
[0043] Based on this, the present invention provides a method for preparing an ultraviolet long afterglow nanoluminescent material, referring to Figure 2 , specifically including the following steps:
[0044] S10, mixing rare earth salt, octadecene and oleic acid in sequence to obtain a mixed solution, and heating the mixed solution to achieve the purpose of removing water;
[0045] S20, after the mixed solution is cooled to room temperature, a sodium source, a cesium source and / or a bromine source and / or an iodine source, and a fluorine source are added to the mixed solution in a desired proportion to form a mixed solution, the mixed solution is heated to a first temperature, and stirred at the first temperature, and reacted for a period of time to nucleate nanocrystals to obtain a preliminary product;
[0046] S30, heating the preliminary product to a second temperature, and keeping stirring, and then continuing to heat to a third temperature under an inert gas environment, and keeping the temperature for a period of time, so that the nanocrystals grow and form, to obtain a final product; wherein the second temperature is greater than the first temperature, and the third temperature is greater than the second temperature;
[0047] S40, washing the final product to obtain an ultraviolet long afterglow nano-luminescent material.
[0048] Since the ionic radius of iodine ions is too large, it is very easy to form hydrogen bonds with water molecules in the air. After being doped into the ultraviolet long afterglow nanoluminescent material, the water absorption of the ultraviolet long afterglow nanoluminescent material increases, which is not conducive to long-term storage. Therefore, the present invention takes the doping of cesium ions alone, the doping of bromide ions alone, and the co-doping of cesium ions and bromide ions as examples to introduce specific embodiments. The reagents used in the specific embodiments are all commercially available unless otherwise specified; the methods used in the specific embodiments are all conventional methods that can be implemented unless otherwise specified.
[0049] The solution of the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0050] Example 1
[0051] This embodiment provides an ultraviolet long afterglow nano luminescent material (Cs 0.02 Na 0.98 LuF4:Gd 3+ 20mol% nanocrystals), comprising the following steps:
[0052] S10, mixing rare earth salt, octadecene and oleic acid in sequence, and heating to obtain a mixed solution.
[0053] Specifically, 4 mL of oleic acid and 6 mL of octadecene were mixed and added to a 50 mL two-necked flask; 0.32 mmol of Lu(C2H3O2)3 and 0.08 mmol of Gd(C2H3O2)3 were mixed to prepare a 0.2 M rare earth acetate aqueous solution, and the rare earth acetate aqueous solution was added to the flask to obtain a mixed solution. A stirring bar was added to the flask, and the flask was placed in an oil bath, and the mixed solution was heated to 150° C. under the stirring of the stirring bar, and the stirring was continued for 30 minutes at this temperature to achieve the purpose of removing water.
[0054] S20, after the mixed solution in step S10 is cooled to room temperature, a sodium source, a cesium source and a fluorine source are added to the mixed solution in a molar ratio of 49:1:80 to form a mixed solution, the mixed solution is heated to a first temperature, and stirred at the first temperature, reacting for a period of time to allow the nanocrystals to nucleate, thereby obtaining a preliminary product; wherein the first temperature is 45-55°C, and the stirring time is 20-40 minutes.
[0055] Specifically, stop heating, wait for the mixed solution of step S10 to cool naturally to room temperature, take out the flask from the oil bath and put it into a heating mantle for standby; take 1.96 mL of 0.5 M NaOH methanol solution, 0.04 mL of 0.5 M CsOH methanol solution and 4 mL of 0.4 M NH4F methanol solution, mix and ultrasonicate for 5 seconds to obtain a methanol mixed solution, mix the methanol mixed solution with the mixed solution in the flask to obtain a mixed solution, heat the mixed solution to 50°C, and continue stirring for 30 minutes to perform a low-temperature nucleation reaction to obtain a preliminary product.
[0056] S30, heating the preliminary product to a second temperature and maintaining stirring, then continuing to heat to a third temperature in an inert gas environment and maintaining the temperature for a period of time to allow the nanocrystals to grow and form, thereby obtaining a final product; wherein the second temperature is 90-110°C, the stirring time is 20-40 minutes, the third temperature is 280-300°C, and the insulation time is 80-100 minutes.
[0057] Specifically, the preliminary product of step S20 is heated to 100° C. and stirred for 30 minutes to remove excess methanol, and then evacuated using a vacuum pump. Subsequently, the preliminary product is quickly heated to 290° C. under nitrogen protection and kept warm for 90 minutes to crystallize the preliminary product to obtain the final product.
[0058] S40, washing the final product to obtain an ultraviolet long afterglow nano luminescent material (Cs 0.02 Na 0.98 LuF4:Gd 3+ 20mol% nanocrystals).
[0059] Specifically, after the reaction in step S30 was completed, the temperature of the final product was cooled to room temperature, 6 mL of anhydrous ethanol was added to the final product, and then centrifuged at 6000 rpm for 5 minutes, the supernatant was discarded to obtain a product precipitate, the product precipitate was dissolved in 4 mL of cyclohexane, and then washed twice with ethanol to obtain an ultraviolet long afterglow nanoluminescent material (Cs 0.02 Na 0.98 LuF4:Gd 3+ 20mol% nanocrystals).
[0060] Example 2
[0061] This embodiment provides a long afterglow ultraviolet nano-luminescent material (NaLu (F 0.98 Br 0.02 )4: Gd 3+ The preparation method of the nanocrystal (20 mol % nanocrystal) is similar to the preparation method of Example 1, except that step S20 comprises:
[0062] After the mixed solution is cooled to room temperature, a sodium source methanol solution, a fluorine source methanol solution and a bromine source methanol solution are added to the mixed solution to form a mixed solution, and the mixed solution is heated to perform a nucleation reaction to obtain a preliminary product; wherein the molar ratio of the sodium source, the fluorine source and the bromine source is 250:8:392, that is, the methanol mixed solution in step S20 is prepared by mixing 2 mL of a 0.5 M NaOH methanol solution, 0.08 mL of a 0.4 M NH4Br methanol solution and 3.92 mL of a 0.4 M NH4F methanol solution.
[0063] Example 3
[0064] This embodiment provides an ultraviolet long afterglow nano luminescent material (Cs 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ 20mol% nanocrystals), comprising the following steps:
[0065] S10, mixing rare earth salt, octadecene and oleic acid in sequence, and heating to obtain a mixed solution.
[0066] Specifically, 4 mL of oleic acid and 6 mL of octadecene were mixed and added to a 50 mL two-necked flask; 0.32 mmol of Lu(C2H3O2)3 and 0.08 mmol of Gd(C2H3O2)3 were mixed to prepare a 0.2 M rare earth acetate aqueous solution, and the rare earth acetate aqueous solution was added to the flask to obtain a mixed solution. A stirring bar was added to the flask, and the flask was placed in an oil bath, and the mixed solution was heated to 150° C. under the stirring of the stirring bar, and the stirring was continued for 30 minutes at this temperature to achieve the purpose of removing water.
[0067] S20, after the mixed solution in step S10 is cooled to room temperature, a sodium source, a cesium source, a bromine source and a fluorine source are added to the mixed solution in a molar ratio of 245:5:8:392 to form a mixed solution, the mixed solution is heated to a first temperature, and stirred at the first temperature to react for a period of time to nucleate the nanocrystals to obtain a preliminary product; wherein the first temperature is 45-55°C, and the stirring time is 20-40 minutes.
[0068] Specifically, stop heating, wait for the mixed solution of step S10 to cool naturally to room temperature, take out the flask from the oil bath and put it into a heating mantle for standby; take 1.96 mL of 0.5 M NaOH methanol solution, 0.04 mL of 0.5 M CsOH methanol solution, 0.08 mL of 0.4 M NH4Br methanol solution and 3.92 mL of 0.4 M NH4F methanol solution, mix and ultrasonicate for 5 seconds to obtain a methanol mixed solution, mix the methanol mixed solution with the mixed solution in the flask to obtain a mixed solution, heat the mixed solution to 50°C, and continue stirring for 30 minutes to perform a low-temperature nucleation reaction to obtain a preliminary product.
[0069] S30, heating the preliminary product to a second temperature and maintaining stirring, then continuing to heat to a third temperature in an inert gas environment and maintaining the temperature for a period of time to allow the nanocrystals to grow and form, thereby obtaining a final product; wherein the second temperature is 90-110°C, the stirring time is 20-40 minutes, the third temperature is 280-300°C, and the insulation time is 80-100 minutes.
[0070] Specifically, the preliminary product of step S20 is heated to 100° C. and stirred for 30 minutes to remove excess methanol, and then evacuated using a vacuum pump. Subsequently, the preliminary product is quickly heated to 290° C. under nitrogen protection and kept warm for 90 minutes to crystallize the preliminary product to obtain the final product.
[0071] S40, washing the final product to obtain an ultraviolet long afterglow nano luminescent material (Cs 0.02 Na 0.98 LuF4:Gd 3+ 20mol% nanocrystals).
[0072] Specifically, after the reaction in step S30 was completed, the temperature of the final product was cooled to room temperature, 6 mL of anhydrous ethanol was added to the final product, and then centrifuged at 6000 rpm for 5 minutes, the supernatant was discarded to obtain a product precipitate, the product precipitate was dissolved in 4 mL of cyclohexane, and then washed twice with ethanol to obtain an ultraviolet long afterglow nanoluminescent material (Cs 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ 20mol% nanocrystals).
[0073] Morphology characterization: The ultraviolet long afterglow nanoluminescent material (Cs 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+20 mol% nanocrystals) were dissolved in 4 mL of cyclohexane to obtain a nanomaterial solution, which was dropped onto a copper mesh. After drying, the morphology was tested by transmission electron microscopy. Figure 3-4 As shown, it can be found that the prepared ultraviolet long afterglow nanoluminescent material (Cs 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ 20mol% nanocrystals) are uniform in size and well dispersed, with an average particle size of about 58nm.
[0074] Example 4
[0075] This embodiment provides an ultraviolet long afterglow nano luminescent material (Cs 0.02 Na 0.98 Lu(F 0.99 Br 0.01 )4: Gd 3+ The preparation method of the nanocrystal (20 mol% nanocrystal) is similar to the preparation method of Example 3, except that, in step S20, the molar ratio of the sodium source, the cesium source, the bromine source and the ammonium source is 245:5:4:396, that is, the methanol mixed solution in step S20 is prepared by mixing 1.96 mL of 0.5 M NaOH methanol solution, 0.04 mL of 0.5 M CsOH methanol solution, 0.04 mL of 0.4 M NH4Br methanol solution and 3.96 mL of 0.4 M NH4F methanol solution.
[0076] Example 5
[0077] This embodiment provides an ultraviolet long afterglow nano luminescent material (Cs 0.02 Na 0.98 Lu(F 0.97 Br 0.03 )4: Gd 3+ The preparation method of the nanocrystal (20mol%) is similar to the preparation method of Example 3, except that, in step S20, the molar ratio of the sodium source, the cesium source, the bromine source and the ammonium source is 245:5:12:388, that is, the methanol mixed solution in step S20 is prepared by mixing 1.96mL of 0.5M NaOH methanol solution, 0.04mL of 0.5M CsOH methanol solution, 0.12mL of 0.4M NH4Br methanol solution and 3.88mL of 0.4M NH4F methanol solution.
[0078] Example 6
[0079] This embodiment provides an ultraviolet long afterglow nano luminescent material (Cs 0.02 Na 0.98Lu(F 0.96 Br 0.04 )4: Gd 3+ The preparation method of the nanocrystal (20mol%) is similar to the preparation method of Example 3, except that, in step S20, the molar ratio of the sodium source, the cesium source, the bromine source and the ammonium source is 245:5:16:384, that is, the methanol mixed solution in step S20 is prepared by mixing 1.96mL of 0.5M NaOH methanol solution, 0.04mL of 0.5M CsOH methanol solution, 0.16mL of 0.4M NH4Br methanol solution and 3.82mL of 0.4M NH4F methanol solution.
[0080] Comparative Example 1:
[0081] Comparative Example 1 provides a long afterglow ultraviolet nano-luminescent material (NaLuF4:Gd 3+ The preparation method of the nanocrystal (20 mol % nanocrystal) is similar to the preparation method of Example 1, except that step S20 comprises:
[0082] After the mixed liquid is cooled to room temperature, a sodium source methanol solution and a fluorine source methanol solution are added to the mixed liquid to form a mixed solution, and the mixed solution is heated to perform a nucleation reaction to obtain a preliminary product; wherein the molar ratio of the sodium source to the fluorine source is 5:8, that is, the methanol mixed solution in step S20 is prepared by mixing 2 mL of a 0.5 M NaOH methanol solution and 4 mL of a 0.4 M NH4F methanol solution.
[0083] Test example 1:
[0084] The ultraviolet long afterglow nanoluminescent materials obtained in Example 1, Examples 3-6 and Comparative Example 1 were dried and ground into powders for X-ray diffraction (XRD) characterization.
[0085] like Figure 5 As shown, the ultraviolet long afterglow nanoluminescent material (Cs x Na 1-x Lu(F 1-y Z y )4: Gd 3+ Nanocrystals) are pure phase, do not contain any impurities, and are doped with Cs + and / or Br - After that, each peak in XRD has a small angle shift, proving that NaLuF4:Gd 3+ 20mol% nanocrystals have been successfully doped with Cs + and / or Br - .
[0086] Test example 2:
[0087] The thermoluminescence curves of the ultraviolet long afterglow nanoluminescent materials obtained in Examples 1-3 and Comparative Example 1 were detected.
[0088] like Figure 6 As shown, doped Cs + After Cs 0.02 Na 0.98 LuF4:Gd 3+ The thermoluminescence signal of 20mol% nanocrystals is enhanced at around 335℃ and 535℃, and the Br-doped - After NaLu (F 0.98 Br 0.02 )4: Gd 3+ The thermoluminescence signal of 20mol% nanocrystals is enhanced at around 350℃ and 625℃, indicating that single doping with cesium ions and single doping with bromide ions can form new electron traps in the matrix. + and Br - After Cs 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ The thermoluminescence signal of 20mol% nanocrystals is significantly enhanced in the range of 350℃-650℃, that is, the density of deep and shallow traps in the ultraviolet long afterglow nanoluminescent materials is significantly increased after co-doping with cesium ions and bromide ions, indicating that the synergistic effect of cesium ions and bromide ions forms new electron traps in the matrix. Under the stimulation of external light, electrons are captured in large quantities by the electron traps of cesium ions and bromide ions, forming a strong thermoluminescence signal.
[0089] Test example 3:
[0090] The long afterglow decay curves of the ultraviolet long afterglow nanoluminescent materials obtained in Example 1 and Example 3 were detected.
[0091] like Figure 7 As shown, Cs + and Br - Cs 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ The afterglow time of 20mol% nanocrystals reaches more than 30000s, which is stronger than that of single doped Cs + Cs 0.02 Na 0.98 LuF4:Gd 3+ Afterglow performance of 20mol% nanocrystals. Test Example 4:
[0092] The radiation luminescence curves of the ultraviolet long afterglow nano-luminescent materials obtained in Examples 1-6 and Comparative Example 1 were detected.
[0093] like Figure 8 As shown in the figure, the radiation luminescence performance of the ultraviolet long afterglow nanoluminescent materials doped with cesium ions alone, bromide ions alone and cesium and bromide co-doped are all stronger than that of the undoped ultraviolet long afterglow nanoluminescent materials, while the radiation luminescence performance of the ultraviolet long afterglow nanoluminescent materials co-doped with cesium and bromide is stronger than that of the ultraviolet long afterglow nanoluminescent materials doped with cesium ions alone and bromide ions alone. Therefore, doping Cs + and / or Br - It can significantly improve the radiation luminescence intensity of ultraviolet long afterglow nano luminescent materials.
[0094] In addition, in Examples 3-6, Cs 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ The luminescence intensity of 20mol% nanocrystals is the highest, followed by Cs 0.02 Na 0.98 Lu(F 0.97 Br 0.03 )4: Gd 3+ 20mol% nanocrystals.
[0095] Test example 5:
[0096] The afterglow decay curves of the ultraviolet long afterglow nanoluminescent materials obtained in Examples 1-6 and Comparative Example 1 were detected.
[0097] See also Fig. 9 The afterglow performance of the ultraviolet long afterglow nanoluminescent materials doped with cesium ions alone, bromide ions alone and cesium and bromide co-doped are all stronger than that of the undoped ultraviolet long afterglow nanoluminescent materials, while the afterglow performance of the ultraviolet long afterglow nanoluminescent materials co-doped with cesium and bromide is stronger than that of the ultraviolet long afterglow nanoluminescent materials doped with cesium ions alone and bromide ions alone. + and / or Br - It can significantly improve the afterglow intensity of ultraviolet long afterglow nano luminescent materials.
[0098] In addition, in Examples 3-6, Cs 0.02 Na 0.98 Lu(F 0.98 Br 0.02 )4: Gd 3+ The afterglow intensity of 20mol% nanocrystals is the highest, followed by Cs 0.02 Na 0.98 Lu(F 0.97 Br 0.03 )4: Gd 3+ 20mol% nanocrystals and Cs 0.02 Na 0.98 Lu(F0.96 Br 0.04 )4: Gd 3+ 20mol% nanocrystals.
[0099] In summary, the present invention has the following advantages compared with the prior art:
[0100] 1. The present invention proposes a simple and repeatable co-doping process by simultaneously introducing cesium ions (Cs + ) and bromide ion (Br - ) or iodide ion (I - ), can to a certain extent avoid the individual limitations of cesium ion and halogen anion doping on their crystal field environment, so that the two can synergistically enhance the ultraviolet long afterglow nanoluminescent materials and achieve the effect of enhancing the luminescent performance of the materials.
[0101] 2. Cesium ions have a larger atomic weight than sodium ions, so they can enhance the absorption capacity of ultraviolet long afterglow nanoluminescent materials to X-rays. This characteristic makes the ultraviolet long afterglow nanoluminescent materials prepared by the present invention have potential advantages in X-ray imaging and detection.
[0102] 3. Bromide ions and iodide ions have larger ion radius than fluoride ions. Their introduction in appropriate amounts will lead to lattice mismatch in ultraviolet long afterglow nanoluminescent materials, resulting in greater trap density and deeper traps. However, their excessive introduction will cause changes in the crystal field environment that are not conducive to the luminescence of rare earth ions, affecting the luminescence performance. The present invention adjusts the amount of their introduction so that the doping ratio of cesium ions and halogen anions has a positive effect on the material properties.
[0103] 4. The co-doping process proposed in the present invention can regulate the generation of traps in fluoride nanocrystals under X-ray irradiation, thereby improving the luminescence and afterglow performance of the material, and is expected to make the material have a wider application potential in X-ray information storage and encryption.
[0104] 5. The present invention proposes a simple and repeatable preparation process, which can stably prepare ultraviolet long afterglow nanoluminescent materials with excellent performance by precisely controlling the molar ratio of reactants and reaction conditions.
[0105] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0106] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An ultraviolet long afterglow nanoluminescent material, characterized in that: The invention comprises a fluoride matrix and rare earth ions Gd doped in the fluoride matrix. 3+ , the rare earth ion Gd 3+ The doping amount is 15-25 mol%; the fluoride matrix is ALuB4; wherein A is selected from Na or Cs x Na 1-x , x is the doping ion Cs + Relative alkali metal ion Na + The molar percentage coefficient; B is F 1-y Z y , y is the doping ion Z - Relative halogen ion F - The molar percentage coefficient has a value range of 0.01≤y≤0.04, and Z is selected from at least one of Br and I.
2. The ultraviolet long afterglow nanoluminescent material according to claim 1, characterized in that: A for Cs x Na 1-x , the value range of x is 0.01≤x≤0.
04.
3. The ultraviolet long afterglow nanoluminescent material according to claim 2, characterized in that: The average particle size of the ultraviolet long afterglow nano luminescent material is 55nm-60nm.
4. A method for preparing an ultraviolet long afterglow nanoluminescent material, characterized in that: The steps include: S10, mixing rare earth salt, octadecene and oleic acid in sequence, and heating to obtain a mixed solution; S20, after the mixed solution is cooled to room temperature, a sodium source, a fluorine source, and a cesium source and / or a bromine source and / or an iodine source are added to the mixed solution to form a mixed solution, and the mixed solution is heated to a first temperature and kept stirred to obtain a preliminary product; S30, heating the preliminary product to a second temperature, and maintaining stirring, and then continuing to heat to a third temperature under an inert gas environment, and maintaining the temperature, to obtain a final product; S40, washing the final product to obtain an ultraviolet long afterglow nano-luminescent material; The second temperature is greater than the first temperature, and the third temperature is greater than the second temperature.
5. The preparation method according to claim 4, characterized in that: In step S20, the mixed solution contains a sodium source, a cesium source, a bromine source and / or an iodine source, and a fluorine source in a molar ratio of 240-250:0-10:4-20:380-396.
6. The preparation method according to claim 5, characterized in that: In step S20, the first temperature is 45-55°C, and the stirring time is 20-40 minutes.
7. The preparation method according to claim 5, characterized in that: In step S10, the heating includes heating the mixed solution to 140-160°C and continuously stirring at the temperature for 30 minutes.
8. The preparation method according to claim 7, characterized in that: In step S10, the rare earth salt includes a lutetium source and a gadolinium source in a molar ratio of 4:
1.
9. The preparation method according to claim 4, characterized in that: In step S30, the second temperature is 90-110°C, the stirring time is 20-40 minutes, the third temperature is 280-300°C, and the insulation time is 80-100 minutes.
10. The preparation method according to any one of claims 4 to 9, characterized in that: In step S20, a sodium source, a cesium source, a bromine source, and a fluorine source are added to the mixed solution, and the molar ratio of the sodium source, the cesium source, the bromine source, and the fluorine source is 245:5:8-12:388-392.